KONSEP PENERAPAN HAKAM DALAM MEDIASI DILUAR PENGADILAN PERSPEKTIF Q.S. AL NISA’ AYAT 35 DAN HADITS (Studi Kasus Desa Sumbermulyo Kecamatan Jogoroto Kabupaten Jombang) - Mohammad Brilyan Aqil Alkhowarizmi (JURNAL ILMIAH NUSANTARA, 2025)
Islam is a religion that upholds peace, messages of brotherhood in the name of love and humanity are so clear and are widely stated in the holy book of the Qur'an. Islam strongly emphasizes that its people strengthen the bonds of brotherhood while spreading goodness to others, it is undeniable that there are still people who like to live in disunity rather than harmony and peace. The Qur'an provides regulations as an alternative dispute resolution in mediating conflicts between fellow Muslims that occur later reinforced in the relevant Hadith.